2016
DOI: 10.1016/j.jchromb.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the technical variations and the suitability of a hydrophilic interaction liquid chromatography-high resolution mass spectrometry (ZIC-pHILIC-Exactive orbitrap) for clinical urinary metabolomics study

Abstract: Evaluation of the technical variations and the suitability of a hydrophilic interaction liquid chromatography-high resolution mass spectrometry (ZIC-pHILIC-Exactive orbitrap) for clinical urinary metabolomics study. Journal of Chromatography B, 1022Chromatography B, , pp. 199-205. (doi:10.1016Chromatography B, /j.jchromb.2016 This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(1 reference statement)
1
2
0
Order By: Relevance
“…The analysis of the QC samples will reflect the system variation. As described in literature, to be reliable, RSD values for the resolved features have to be below 30% for the AUC values and below 5% for the migration times [46]. In this study, 44 measured m/z values in the QC samples showed acceptable RSD values (below 20.3% for the corrected areas and below 2.5% for the migration times).…”
Section: Evaluation Of Analytical Workflow For Metabolic Profiling Of Volumerestricted Plasma Samplessupporting
confidence: 65%
“…The analysis of the QC samples will reflect the system variation. As described in literature, to be reliable, RSD values for the resolved features have to be below 30% for the AUC values and below 5% for the migration times [46]. In this study, 44 measured m/z values in the QC samples showed acceptable RSD values (below 20.3% for the corrected areas and below 2.5% for the migration times).…”
Section: Evaluation Of Analytical Workflow For Metabolic Profiling Of Volumerestricted Plasma Samplessupporting
confidence: 65%
“…LC-MS analysis was performed on a Vanquish ultra-high performance liquid chromatography system coupled to a Q Exactive mass spectrometer (Thermo) that was equipped with an Ion Max source and HESI II probe adapting previously described methods 24,25 . External mass calibration was performed every seven days.…”
Section: Methodsmentioning
confidence: 99%
“…Study II (Table ) focused on more subtle differences by spiking the ‘markers’ in both groups with concentrations which differ by a factor 2 between both classes (Table ), and with the absence of one compound in each class. For comparative metabolic profiling only compounds with RSD values for migration time and corrected peak area below 5 and 30%, respectively, as calculated for each class including QC samples ( n = 23), were considered for data analysis as those with higher values may be considered as spurious signals . Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%